Penerapan Sistem Informasi Akuntansi Dalam Peningkatan Efisiensi Pada Pelayanan Rawat Inap Di UPTD Puskesmas Hiliweto Gido - Tree Engel Natalia; Marliyah (Universitas Sains dan Teknologi Komputer, 2024)
Every information related to accounting is handled by the Accounting Information System. (AIS). The purpose of this study was to assess whether the accounting information system at the UPTD Hiliweto Gido Health Center has been implemented successfully and efficiently, and to examine the function of the system in inpatient services. The research methodology of this study uses an exploratory qualitative approach, specifically by using the Google Scholar internet database to obtain secondary data from national papers and conducting focused interviews. The results of this study are that the installation of the accounting information system at the Hiliweto Gido Health Center has been successful based on research findings. This study examines how a more integrated and real-time accounting information system can improve the efficiency of inpatient services at the Health Center, especially in resource management and financing.